Synthesis and Characterisation of Carbon Aerogel Derived from Carboxymethyl Cellulose as Hydrogen Storage Material - Ahmad Solehin Ab Sabar; Syaza Azhari; Nur Atiqah Nasir; Muhammad Zamir Othman (Penerbit Universiti Sains Malaysia (USM Press), 2024)
Indexed by Scopus/MyCite